Application of HPV DNA testing in follow-up after loop electrosurgical excision procedures in Northern Thailand - Surapan Khunamornpong (2018)
Background: HPV DNA testing has been recently introduced as an adjunct test to cytology in the follow-up of patients after treatment for cervical lesions using the loop electrosurgical excision procedure (LEEP). The aim of this study was to evaluate the role of HPV testing in the detection of persistent or recurrent disease after LEEP in patients with cervical epithelial lesions in northern Thailand. Materials and Methods: Patients who underwent LEEP as a treatment for histological low-grade (LSIL) or high-grade squamous intraepithelial lesion (HSIL) or worse at Chiang Mai University Hospital between June 2010 and May 2012 were included. Follow-ups were scheduled at 6-month intervals and continued for 2 years using co-testing (liquid-based cytology and Hybrid Capture 2 [HC2]) at 6 months and 24 months and liquid-based cytology alone at 12 and 18 months. Results: Of 98 patients included, the histological diagnoses for LEEP included LSIL in 16 patients, and HSIL or worse in 82 patients. The LEEP margin status was negative in 84 patients (85.7%). At follow-up, 10 patients (10.2%) had persistent/recurrent lesions; 4 among LSIL patients (25.0%) and 6 in the group with HSIL or worse (7.3%). Only 2 of 82 patients (2.4%) with HSIL or worse diagnoses had histological HSIL in the persistent/recurrent lesions. Using histologically confirmed LSIL as the threshold for the detection of persistent/recurrent disease, cytology had a higher sensitivity than HC2 (90.0% versus 70.0%). At the 6-month follow-up appointment, combined cytology and HC2 (co-testing) had a higher sensitivity in predicting persistent/recurrent disease (80.0%) compared with that of cytology alone (70.0%) and HC2 (50.0%). Conclusions: After LEEP with a negative surgical margin, the rate of persistent/recurrent lesions is low. The addition of HPV testing at the 6-month visit to the usual cytology schedule may be an effective approach in the follow-up after LEEP.